Konstruksi Sosok Perjuangan Mgr. Albertus Soegijapranata, S.J dalam Film Soegija - Kristianingrum, Maria Desi (Jurnal The Messenger, 2013)
Maria Desi Kristianingrum, 2013, the figure Struggle Construction Mgr. Albertus Soegijpranata, SJ in Film Seogija, Department of Communication Studies, Faculty of Opera-and Communication Technology, University of Semarang.This study aims to determine the construction of the figure of the struggle Mgr. Albertus Soegjipranata, S.J in Film Soegija. The hypothesis of this study are: a) estimated a figure of media constructions struggle Mgr. Albertus Seogijapranata, SJ in the film Soegija, b) estimated the fact that minus, plus and highlighted through the storyline is presented.Object samples taken as many as 12 scenes using data collection techniques. Researchers collected data to analyze and scrutinize the data in the form of a movie scene scene per scene. Data analysis is done by using framing your analysis. The results of this study indicate that the reality of the struggle figure Mgr. Albertus Seogijapranata, SJ in the frame by the media is to reduce and add to the actual facts, and packaged in a simple and interesting.